Efficacy of repetitive transcranial magnetic stimulation in post-stroke cognitive impairment: an overview of systematic reviews - Zhang, Linli; Gao, Shan; Wang, Chengshuo; Li, Yuanyuan; Yuan, Huateng; Cao, Longjun; Gao, Chong (Frontiers in Neurology, 2024)
Objective The reliability of clinical evidence depends on high-quality meta-analyses/ systematic reviews (MAs/SRs). However, there has been no assessment of the quality of MAs/SRs for repetitive transcranial magnetic stimulation (rTMS) in post-stroke cognitive impairment (PSCI), both nationally and internationally. This article seeks to use radar plotting to visually present the quality of MAs/SRs on rTMS for improving cognitive function in PSCI, aiming to offer an intuitive foundation for clinical research. Methods Eight Chinese or English databases were systematically searched to collect comprehensive literature, and the retrieval time ranged from inception to 26 March 2024. Literature ranking was calculated using six dimensions: publication year, design type, AMSTAR-2 score, PRISMA score, publication bias, and homogeneity. Finally, radar plots were drafted to present a multivariate literature evaluation. The GRADE tool assessed the strength of evidence for the outcome indicators included in the MAs/SRs. Results The 17 articles included had average scores of 12.29, 17, 9.88, 9.71, 12.88, and 12.76 for each dimension. The radar plot showed that an article published in 2023 had the highest rank and a large radar plot area, while an article published in 2021 had the lowest rank and a small radar plot area. The GRADE tool evaluation revealed that 51 pieces of evidence were of very low quality, 67 were of low quality, 12 were of moderate quality, and only one was of high quality. Conclusion The average rank score of literature ranged from 8.50 to 17, with higher rankings indicating greater significance in literature reference. Variations in literature quality were attributed to inadequate study planning, irregular literature search and screening, insufficient description of inclusion criteria for studies, and inadequate consideration of bias risk in the included studies. Most MAs/SRs indicated that rTMS was more effective than the control group in enhancing the global cognitive function and activities of daily living in PSCI patients. However, the overall quality of the literature was generally low and needs validation from future high-quality evidence. Systematic review registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42023491280.